Leading and innovating sustainable business development - Nguyen, Dinh Tho (VNU - HCM Press, 2017)
Đầu trang tên sách ghi : Institute for Computational Science and Technology, Ho Chi Minh City - University of Natural Resource and Environment, Nihon University (Japan); TM tham khảo cuối bài